Evaluations of Antioxidant Enzyme Activities, Total Sialic Acid and Trace Element Levels in Coronary Artery Bypass Grafting Patients - Yildiz,Damla (2021)
Abstract Introduction: In this study, patients before and after cardiac surgery with cardiopulmonary bypass (CPB) and control subjects were evaluated for erythrocyte glutathione peroxidase, catalase and superoxide dismutase enzyme activities, in addition to glutathione, malondialdehyde, serum total sialic acid, lipid-bound sialic acid, total antioxidant status, trace elements and mineral levels. The correlation of these variables with coronary artery disease (CAD) was also assessed. Methods: A total of 30 CAD patients and 30 control subjects were included in the study. CAD patients were divided into three groups: before surgery (BS), first day after surgery (1st day AS) and seventh day after surgery (7th day AS). Results: Malondialdehyde (MDA) and total sialic acid (TSA) levels were significantly higher in CAD (BS) than in the control group (P<0.05, P<0.05). In addition, GSH and TAS levels were significantly lower in the 1st day AS group than in the control group (P<0.001, P<0.01). Moreover, Co, Cu, Mg, Se, V and Zn levels were significantly lower in CAD (BS) group than in the control group (P<0.01, P<0.01, P<0.01, P<0.01, P<0.05, P<0.001). Conclusions: It was concluded that the levels of LDL-C, total cholesterol, triglycerides and CRP significantly associated with parameters, as well as Cu, Ca and SOD activity, should be measured together to monitor CAD. It is also considered that measuring TSA and MDA might be an appropriate choice for biomarkers of CAD.